ChemInform Abstract: Gold‐Catalyzed Proto‐ and Deuterodeboronation. Issue 10 (February 2016) - Barker, Graeme; Webster, Stacey; Johnson, David G.; Curley, Rachel; Andrews, Matthew; Young, Paul C.; Macgregor, Stuart A.; Lee, Ai‐Lan
Abstract: A Au(I)‐catalyzed protodeboration of a variety of arylboronic acids using dimethylcarbonate as the solvent is presented.